A fuzzy query evaluation technique for relational databases - Nadia Mat Amin (Fakulti Sains dan Teknologi, 2011)
The current querying process in Structured Query Language (SQL) is inflexible and rigid. It is based solely on text matching process between the query text and the available index texts in the database and this led to frequent frustration among the users. Therefore, providing some flexibility to SQL can help users to improve their interaction with the system. This research presents a new way of querying color from a relational database, based on the fuzzy logic technique and a-cut operation, and by using the approach of generalization of strategies for fuzzy query translation in relational databases.